Authentic Assessment Instrument: Implementation of Performance-Based Practicum - Risma Agustina; Madziatul Churiyah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
The purpose of this study was to develop an authentic performance-based assessment instrument in a proper Archival Management course through expert validation and product trials that have been carried out at State University of Malang and meet the National Standards of Higher Education. The research method used Research and Development which was modified into 7 steps with data analysis techniques using mean. Products developed include assessment instruments that were equipped with Student Worksheets, performance observation sheets, and guidelines for scoring criteria. Based on content validation and construct produce works with very decent criteria, the trial conducted by lecturers and students stated that the instrument could be used very easily.